Robust Switched State Feedback design for linear uncertain systems subject to disturbances - Faria, Flavio Andrade; Barroso, Mateus Aquila; Lazarini, Adalberto Zanatta Neder; Assuncao, Edvaldo; Cardim, Rodrigo; Teixeira, Marcelo Carvalho Minhoto (Proceedings (IEEE International Workshop on Variable Structure Systems), 2022)
A state feedback design for linear uncertain sys-tems is proposed. To attenuate the effect of disturbances on the output of the system two performance indexes are included in the control design. For \mathcal{L}_{2} disturbances the results ensures that the closed loop system has an \mathcal{H}_{∞} guaranteed cost and for \mathcal{L}_{∞} disturbances a L 1 performance index is achieved. The stabilization conditions are given in terms of LMIs. To improve the control performance and relax the LMI conditions a switched controller which avoids chattering is proposed. Numerical examples illustrate the efficiency of the stabilizing conditions.